2020
DOI: 10.20944/preprints202003.0427.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Natural Immune Boosters as First-Line Armours to Combat Viral Infection-COVID19: Myth or Science?

Abstract: The coronavirus COVID-19 epidemic has wreaked havoc on inhabitants of earth killing thousands of humans from more than 150 countries. The epidemic has put a number of countries under complete lockdown and the deadly situation is still prevailing around the globe. Vaccines have been long known as the most effective means of preventing viral infections. However, the lack of vaccines against COVID-19 has further worsened the situation. In this time of health crisis, it is the duty of scientific research community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The mounting substantiation reveals that having healthy lifestyle, natural food products can boost the immune functions of the body to combat the severity of viral infections. While, improving the immune responses they also provide resistance against pathogenic organisms ( Sarfraz et al, 2020 ).…”
Section: Ancillary Armours To Combat Covid-19 Viral Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mounting substantiation reveals that having healthy lifestyle, natural food products can boost the immune functions of the body to combat the severity of viral infections. While, improving the immune responses they also provide resistance against pathogenic organisms ( Sarfraz et al, 2020 ).…”
Section: Ancillary Armours To Combat Covid-19 Viral Infectionmentioning
confidence: 99%
“…Majority of these attributes are linked to reboot the functions associated with improved immunity via mediating anti-inflammatory activities, enhancing cell-mediated immune functions, modulated APC (Antigen Presenting Cell) activities and suppressing pro-inflammatory mediators. In addition, they also mediate effective cell-cell communication during innate as well as adaptive immune responses ( Sarfraz et al, 2020 ). Hence, a scientific expedition of escalating immune system through appropriate sleep, judicious exercise, stress-free environment, proper nutritive foods, water intake and consumption of fresh and healthy fruits and vegetables would anticipate the citizenry to cope with coronavirus battle via naturally vaccinating their systems ( Jayawardena et al, 2020 ).…”
Section: Ancillary Armours To Combat Covid-19 Viral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence suggesting that the use of appropriate foods and lifestyle changes plays a key role in disease resistance and health. Sarfraz et al have suggested six steps which might help to protect against respiratory diseases (Sarfraz et al, 2020). In general, proper sleep, moderate exercise, stress avoidance, consuming vitamin-rich foods, fruits and vegetables might naturally help to support the immune system when dealing with viral diseases such as COVID-19.…”
Section: General Recommendation For Immunonutrition and Nutritional Smentioning
confidence: 99%
“…that the market place deemed positive for the coronavirus disease, and there was no specific association with any animal. 24 Is the novel coronavirus similar to SARS and MERS? 76% of the participants agreed the close resemblance similarity to SARS and MERS.…”
Section: Discussionmentioning
confidence: 99%